Metabolic syndrome in children and adolescents with phenylketonuria - Viviane C. Kanufre; Rosângelis D.L. Soares; Michelle Rosa A. Alves; Marcos J.B. Aguiar; Ana Lúcia P. Starling; Rocksane C. Norton (Elsevier, 2015)
OBJECTIVE: This study aimed to identify markers of metabolic syndrome (MS) in patients with phenylketonuria (PKU). METHODS: This was a cross-sectional study consisting of 58 PKU patients (ages of 4-15 years): 29 patients with excess weight, and 29 with normal weight. The biochemical variables assessed were phenylalanine (phe), total cholesterol, HDL-c, triglycerides, glucose, and basal insulin. The patients had Homeostasis Model Assessment (HOMA) and waist circumference assessed. RESULTS: No inter-group difference was found for phe. Overweight patients had higher levels of triglycerides, basal insulin, and HOMA, but lower concentrations of HDL-cholesterol, when compared to the eutrophic patients. Total cholesterol/HDL-c was significantly higher in the overweight group. A positive correlation between basal insulin level and HOMA with waist circumference was found only in the overweight group. CONCLUSION: The results of this study suggest that patients with PKU and excess weight are potentially vulnerable to the development of metabolic syndrome. Therefore, it is necessary to conduct clinical and laboratory monitoring, aiming to prevent metabolic changes, as well as excessive weight gain and its consequences, particularly cardiovascular risk.